An autonomous self-optimizing flow machine for the synthesis of pyridine–oxazoline (PyOX) ligands. Issue 9 (28th March 2019) - Wimmer, Eric; Cortés-Borda, Daniel; Brochard, Solène; Barré, Elvina; Truchet, Charlotte; Felpin, François-Xavier
Abstract : A continuous flow synthesis of PyOX ligands has been developed using an autonomous self-optimizing flow reactor. Abstract : Pyridine–oxazoline-type ligands (PyOX) are an important class of chiral ligands for metal-catalyzed asymmetric transformations. Herein we describe an efficient and reliable flow route which is amenable for the synthesis of PyOX ligands at a scale of hundreds of milligrams per hour. Optimal flow conditions were rapidly identified through the assistance of an in-house built autonomous self-optimizing system integrating a custom-made optimization algorithm derived from the Nelder–Mead and golden section search methods. The preparation of a small library of representative PyOX ligands highlights the practical application of this flow route which should be of primary interest for synthetic chemists developing metal-catalyzed asymmetric transformations.